Quality of LIfe of Hemorrhagic and Ischemic Stroke in Kendary City - Kartika Dewi, Ikaningtyas; Rahmawati, Rahmawati; Yuliastry, Wa Ode (Waluya The International Science of Health Journal, 2025)
Introduction: Stroke is second leading cause of death worldwide which of effect can impact on quality of life. This study aims to analyze correlation hemorrhagic and ischemic stroke impact on quality of life. Method: The research was conducted in retrospective cohort study. Population is 22 hemorrhagic and 28 ischemic stroke patients. Using simple random sampling, the study involved 19 hemorrhagic and 19 ischemic stroke patients. The data was obtained using medical record from Bahteramas Hospital and AqoL-4D questionnaires. Result: 84,2% hemorrhagic stroke patients suffered poor quality of life compared to 15,8% suffered moderate quality of life. 31,6% ischemic stroke patients suffered poor quality of life compared to 68,4% suffered moderate quality of life.Data were analyzed by Chi Square and Relative Risk Test with result hemorrhagic stroke to poor quality of life shows X2:8.744, p:0.003, RR 3.87 (Phi 0.533). Conclusion: The conclusion hemorrhagic stroke is risk factor, as it is 3,87 times more risky in causing poor quality life.